Implementasi Pengelolaan Data Penduduk Berbasis Online Melalui Program Sistem Informasi Administrasi Kependudukan (SIAK) di Distrik Klamono Kabupaten Sorong - Salossa, Asafita Patricia Klasjok; Purnomo, Arie; Fikri, Awal (LRI Universitas Muhammadiyah Sorong, 2025)
In the era of rapid globalization, digital access and technology integration are the keys to advancing a region, even in places far from the city center. Therefore, this study aims to analyze the implementation of the Population Administration Information System in Klamono District, Sorong Regency, Southwest Papua. The Population Administration Information System (SIAK) is a system that manages population data by utilizing information and communication technology. SIAK includes population data collection and civil registration. The Klamono District Government implements the use of SIAK as one form of service approach to the community. SIAK is part of online-based governance that refers to the use of information technology to improve efficiency, transparency and accountability in governance. Thus, this section includes the provision of public services online. The SIAK implementation process in Klamono District has gone well as it should and received a positive response from the community who have benefited from it. However, of course there are still challenges that occur, for that, with various efforts that have been made, it is hoped that the existing challenges can be overcome.